Pendidikan yang Membebaskan dalam Bingkai Filosofi Ki Hajar Dewantara dan Pancasila - Maulani, Silvia Fajar (Universitas Negeri Surabaya, 2025)
The purpose of this research is to analyze the concept of liberating education in the frame of Ki Hajar Dewantara's philosophy and Pancasila values and its relevance in building the character and identity of the Indonesian nation. The research method used in this research is qualitative with the type of Library Research by exploring scientific articles and journals related to Ki Hajar Dewantara's thoughts. The results show that liberating education, which is based on Ki Hajar Dewantara's philosophy and Pancasila values, is able to build the character of students who are independent, nationalist, and have a personality in accordance with the identity of the Indonesian nation. Liberating education, which draws inspiration from Ki Hajar Dewantara, emphasizes respect for each person's uniqueness, individual liberty, and freedom of thought. This is consistent with Pancasila values, which form the basis of an equitable and moral Indonesian educational system.